2008
DOI: 10.1017/s000711450802744x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways leading to early growth faltering: an investigation into the importance of mucosal damage and immunostimulation in different socio-economic groups in Nepal

Abstract: Early childhood growth retardation persists in developing countries despite decades of nutritional interventions. Adequate food is necessary, but not sufficient, to ensure normal growth where there is ubiquitous exposure to infection. Pathways associated with infection, small intestinal mucosal damage and chronic immunostimulation remain largely undemonstrated in countries other than The Gambia. We conducted a longitudinal study of one squatter and one middle-class group (n 86, 3 -18 month olds) to assess thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 20 publications
(31 reference statements)
0
55
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Furthermore, these findings provide further validation of the use of the EE score as composite marker of EE in children. The lack of a significant association between geophagy and alpha-1-antitrypsin, myeloperoxidase, and neopterin is likely a reflection of our small sample size and the EE score representing a more comprehensive measure of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10] Furthermore, these findings provide further validation of the use of the EE score as composite marker of EE in children. The lack of a significant association between geophagy and alpha-1-antitrypsin, myeloperoxidase, and neopterin is likely a reflection of our small sample size and the EE score representing a more comprehensive measure of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 59%
“…1 There is a growing body of literature indicating an association between stunting and environmental enteropathy (EE), a disorder defined by abnormal intestinal morphology, reduced intestinal barrier function, and increased inflammation. [2][3][4][5][6][7][8][9][10] Although its etiology is not fully defined, EE is thought to be caused by unsanitary environmental conditions leading to repeated exposures to enteric pathogens. 11 The gold standard to measure EE is endoscopy and biopsy, which is impractical in most low-income settings.…”
Section: Introductionmentioning
confidence: 99%
“…5 Despite the growing literature demonstrating that EE is associated with impaired growth in children, there is limited information on environmental risk factors for EE. [5][6][7][8][9][10][11][12][13] A previous study in Zimbabwe found that individuals of a lower economic status excreted significantly less xylose, a measure of intestinal absorption, than those individuals of a higher economic status. 18 A more recent study in rural Bangladesh found that children residing in "contaminated" environments *Address correspondence to Christine Marie George, Department of International Health, Johns Hopkins University, 615 N. Wolfe Street, Room E5535, Baltimore, MD 21205-2103.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7][8][9][10][11][12][13] This disorder is defined by abnormal intestinal morphology, including villous atrophy and crypt hyperplasia, which leads to reduced intestinal barrier function and increased inflammation. 7,8,14 EE is thought to arise from unsanitary environmental conditions that lead to repeated exposure to enteric pathogen causing chronic infections.…”
Section: Introductionmentioning
confidence: 99%
“…- Rosalind Gibson presented a model that highlights the synergism and interaction between an inadequate diet and infection in driving linear growth failure [12]. …”
Section: Panel Discussionmentioning
confidence: 99%